Bilateral neck of femur fracture induced by osteomalacia secondary to phosphaturic mesenchymal tumor of paranasal sinus: a case report - V., Shamseer K.; Nambiar, Radhesh (International Journal of Research in Orthopaedics, 2025)
Phosphaturic mesenchymal tumors (PMTs) are rare, often occult neoplasms that cause tumor-induced osteomalacia (TIO) due to excessive fibroblast growth factor 23 (FGF23) secretion, leading to phosphate wasting, hypophosphatemia, and impaired bone mineralization. This results in progressive skeletal fragility and increased fracture risk. We present a 53-year-old male with bilateral femoral neck fractures following a trivial fall, accompanied by generalized myalgia. MRI of the hip and pelvis revealed bilateral femoral neck fractures with sclerotic changes in the superior and inferior pubic rami, sacral ala, and bilateral iliac wings. Laboratory investigations confirmed severe hypophosphatemia and osteomalacia. Further imaging and biopsy identified a phosphaturic mesenchymal tumor in the right anterior ethmoidal sinus as the underlying cause. The patient underwent bilateral femoral neck fracture fixation with cannulated cancellous (CC) screws, along with vitamin D and phosphate supplementation. The PMT was surgically resected to correct the metabolic disorder. Postoperatively, the patient demonstrated significant clinical and biochemical improvement. This case highlights the critical need to consider PMT in patients presenting with unexplained fractures and persistent hypophosphatemia. Early detection, surgical resection of the tumor, and appropriate metabolic correction are essential for optimal recovery and fracture healing.